Journeys to Data Mining Experiences from 15 Renowned Researchers - Gaber, Mohamed Medhat; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Data mining, an interdisciplinary field combining methods from artificial intelligence, machine learning, statistics and database systems, has grown tremendously over the last 20 years and produced core results for applications like business intelligence, spatio-temporal data analysis, bioinformatics, and stream data processing. The fifteen contributors to this volume are successful and well-known data mining scientists and professionals. Although by no means an exhaustive list, all of them have helped the field to gain the reputation and importance it enjoys today, through the many valuable contributions they have made. Mohamed Medhat Gaber has asked them (and many others) to write down their journeys through the data mining field, trying to answer the following questions: 1. What are your motives for conducting research in the data mining field? 2. Describe the milestones of your research in this field. 3. What are your notable success stories? 4. How did you learn from your failures? 5. Have you encountered unexpected results? 6. What are the current research issues and challenges in your area? 7. Describe your research tools and techniques. 8. How would you advise a young researcher to make an impact? 9. What do you predict for the next two years in your area? 10. What are your expectations in the long term? In order to maintain the informal character of their contributions, they were given complete freedom as to how to organize their answers. This narrative presentation style provides PhD students and novices who are eager to find their way to successful research in data mining with valuable insights into career planning. In addition, everyone else interested in the history of computer science may be surprised about the stunning successes and possible failures computer science careers (still) have to offer.
Introduction -- Dean Abbott -- Charu Aggarwal -- Michael Berthold -- John Elder -- Chris Clifton -- David Hand -- Cheryl Howard -- Hillol Kargupta -- Dustin Hux -- Colleen McCue -- Geoff McLachlan -- Gregory Piatetsky-Shapiro -- Shusaku Tsumoto -- Graham Williams -- Mohammed J. Zaki.
Keywords: Computer science; Information storage and retrieval systems; Artificial intelligence; Text processing (Computer science; Computer industry; Computer Science; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; Document Preparation and Text Processing; Probability and Statistics in Computer Science; The Computing Profession